(untitled) (Journal of Philosophy, Culture and Political Science, 2018)
The main objective of this paper is to present in the case of Kazakhstan importance of state branding especially in terms of transitional period as branding can contribute to success of country developing process. This article provides some experience of Central Asian States and Countries of Central, Eastern Europe, underlines significance of combining four dimensions of state branding while promoting a country: public diplomacy, foreign direct investment, international tourism and export. Nowadays positive image is a part of international country reputation, both internally and internationally.